Complete plastome of the medicinally important plant, Alstonia scholaris (Apocynaceae). Issue 2 (3rd July 2019) - Jin, Lei; Yang, Jin; Liu, Changkun; He, Mengling
Abstract: Alstonia scholaris is an evergreen tropical tree with significant medicinal values. To better understand its genetic and genomic profiles, we sequenced and assembled the completed plastome of A. scholaris . The plastome is 154, 699 bp in length, consisting of a large (LSC, 85, 364 bp) and a small single-copy region (SSC, 18, 027 bp), which are separated by a pair of inverted repeat regions (IRs, 25, 654 bp). It possesses 116 unique genes (82 protein-coding genes, 30 tRNAs, and 4 rRNAs). Phylogenetic analysis suggests that A. scholaris is sister to the clade including remaining Apocynaceae species.